Organoleptic Quality of Black Bugis Cake Made from Gude Bean Flour as a Substitute for Black Glutinous Rice Flour - Prasanti, Kadek Dita; Kristiana, Nina Indra; Atmaja, I Made Purwa Dana; Hendrayana, Made (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
In this study, pigeon peas will be used as flour and will be used as a basic ingredient in making Bugis cakes. The purpose of this study was to determine the quality of Bugis cakes that use pigeon pea flour as the basic ingredient, using the organoleptic test research method. The methods used to support data collection are experiments, documentation, organoleptic tests, panelists, questionnaires and Likert scales. The data analysis technique used is descriptive qualitative. The research data in the organoleptic test analyzed using the Likert scale showed that sample A got an average score of 65% with good interpretation criteria, sample B got an average score of 81% with very good interpretation criteria and sample C got an average score of 89% with very good interpretation criteria.